10 things I hate about Pinky : Dimple and Rishi #3 - Menon, Sandhya (New York : Simon Pulse, 2020)
Told in two voices, Ashish's friends Pinky and Samir pretend to date during a summer at Cape Cod to achieve their individual goals--especially to get their respective mothers off their backs.
Sequel to: There's something about Sweetie.
Ages 12 and Up.
Grades 7-9.
Keywords: Family life -- Fiction; Dating (Social customs) -- Fiction; East Indian Americans -- Fiction